Interaction between water and city: Historical legacy and transformation of the city of Ji'ning - Guo, Lu (International Planning History Society Proceedings, 2018)
Ji’ning is a famous historic city with a long history and deep cultural accumulation in Shandong Province, China, which was facing serious environmental problems and cultural crisis due to largescale industrial production and coal mining in recent decades. It is necessary to study the historical legacy of Ji'ning in a scientific way, to excavate its context and characteristics, and furthermore to learn from the legacy and explore the way of urban transformation and development. Firstly, the historical context of the city development of Ji'ning is teased out to excavate its driving force. Secondly, the mechanism of the interaction between city and water is excavated with Canal Cultural Period as an example. Based on this, the enlightenment from the historical legacy to the sustainable future of the contemporary city is declared as a conclusion.